Effects of full inversion tillage during pasture renewal on selected soil fertility indices : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Soil Science, Massey University, Palmerston North, New Zealand - Amanor, Yahaya Jebril (Massey University, 2019)
The impacts of using a one-off Full Inversion Tillage (FIT) method at pasture renewal on soil carbon (C) stocks and other agronomic aspects is currently being researched in New Zealand (NZ) pastoral systems, following establishment of multiple field trials in the North and South Island. However, there is currently minimal available research information on the subsequent effects of FIT on soil fertility. Therefore, the first objective of this study was to assess the impact of tillage method (No Tillage, Shallow Tillage and FIT), performed at pasture renewal, on the soil fertility of two contrasting soil types under grazed pasture. The second objective was to estimate the amounts of fertiliser nutrients required to replace the nutrients removed from the 0-7.5 cm soil sampling depth, as a result of FIT. The study involved soil sampling of three trial sites, in the North Island of New Zealand, which were used to assess tillage treatment effects on soil total C and N, pH, Olsen extractable P, exchangeable cations and CEC. The soil sampling was approximately 18, 13 and 8 months following the tillage treatments at Field trials 1, 2 and 3, respectively, and was based on a two-factor factorial design, consisting of three tillage treatments (Field trial 1 or 2: No Tillage (NT), FIT and Shallow Tillage (ST); Field trial 3: NT, FIT and Permanent Pasture (PP)) and four soil depths (0-7.5, 7.5-15, 15-22.5 and 22.5-30 cm). The soil at Field trial 1 and 3 is a Pallic soil and at Field trial 2 is an Allophanic soil. Across the three sites 8-13 months after tillage treatments, the FIT treatment transferred 16- 46% more total C and 24-41% more total N from the 0-7.5 cm soil depth to deeper depths, compared to the NT treatment, but did not change the total C and N stocks in the entire 0-30 cm soil depth. The effect of FIT on soil fertility parameters was only significant for Olsen extractable P, exchangeable K and exchangeable Mg. The FIT treatment reduced soil (0-7.5 cm) Olsen P, exchangeable K and Mg levels by approximately 11-21 mg Olsen P/ha, 0-10.1 MAF QT K and 7-14 MAF QT Mg across the three sites, corresponding to additional P, K and Mg requirements that ranged from 60-120 kg P/ha, 0-1010 kg K/ha and 72-160 kg Mg/ha, respectively. These additional nutrient requirements equate to estimated fertiliser costs that ranged from $210-420/ha, $0-707/ha, and $94-208/ha (excluding transport and spreading costs) for Olsen P, exchangeable Mg and exchangeable K, respectively, across the three field trials. The study found that the total estimated cost of replacing nutrients removed from the topsoil depth (0-7.5 cm) ranged across the sites from $362-1,293/ha. The range in cost is influenced by initial soil fertility levels and the depth and degree of soil inversion implemented. If the initial soil fertility is higher than optimum, then the amount of nutrients required to increase the soil tests to just within the optimum range will be lower than the cost replacement of available nutrients removed from the 0-7.5 cm soil depth.
Keywords: 410601 Land capability and soil productivity